ASPIRASI PENGAMEN USIA SEKOLAH TENTANG PENDIDIKAN DAN PEKERJAAN - Rio Handika; Wahiruddin Wadin; Parlan Parlan (UNIB Press, Universitas Bengkulu, 2020)
Due to the writer’s thoughtfulness and according to many case studies on school age children, when these kids are supposed to go to school, they go to work. Hence, the writer is interested to conduct this research. The aim of this study is to acknowledge the perception, expectation, and efforts of school age street singers on pursuing education in Kelurahan Kebun Keling, District of Teluk Segara, City of Bengkulu. Using qualitative approach, this study was purposefully utilized case study method. Participants consisted from 6 school age street singers; two of them are in elementary school level, two of them are in junior high school level, and the rest are in senior high school level. Data was obtained through depth interview, observation, and documentation techniques; in the end, there would be conclusion drawing. To validate the data, the writer uses triangulation method on subjects, techniques, and period. The result showed that the school age street singers agree on the importance of pursuing formal education. Their perception towards formal education is assuming that one should be easier to achieve their dream jobs through their knowledge gained from their previous education. In continuation, they expect to pursue higher education so that they could get a job effortlessly. However, they have not maximized their effort to pursue better education. These mainly occur because of financial and social factors. Key words: Perception, Expectation, Efforts, and Causal Factors